Adjuvant Immune Checkpoint Inhibitors for Muscle-Invasive Urothelial Carcinoma: An Updated Systematic Review, Meta-analysis, and Network Meta-analysis - Yanagisawa, Takafumi; Mori, Keiichiro; Matsukawa, Akihiro; Kawada, Tatsushi; Katayama, Satoshi; Laukhtina, Ekaterina; Rajwa, Pawel; Quhal, Fahad; Pradere, Benjamin; Fukuokaya, Wataru; Iwatani, Kosuke; Afferi, Luca; et al. (Targeted oncology, 2025)
CONTEXT: Adjuvant immune checkpoint inhibitors (ICIs) have recently emerged as guideline-recommended treatments of high-risk muscle-invasive urothelial carcinoma (MIUC). However, there is limited evidence regarding the optimal candidates and the differential efficacy of adjuvant ICI regimens. OBJECTIVE: To synthesize and compare the efficacy and safety of adjuvant ICIs for high-risk MIUC using updated data from phase III randomized controlled trials. EVIDENCE ACQUISITION: In April 2024, three databases were searched for eligible randomized controlled trials that evaluated oncologic outcomes in patients with MIUC treated with adjuvant ICIs. Pairwise meta-analysis (MA) and network meta-analyses were performed to compare the hazard ratios of oncological outcomes, including disease-free survival (DFS), overall survival (OS), and adverse events. Subgroup analyses were conducted on the basis of predefined clinicopathological features. EVIDENCE SYNTHESIS: Three randomized controlled trials that assessed the efficacy of adjuvant nivolumab, pembrolizumab, and atezolizumab were included in the MAs and network meta-analyses groups. Pairwise MAs showed that treatment with adjuvant ICIs significantly improved DFS [hazards ratio: 0.77, 95% confidence interval (CI): 0.66-0.90] as well as OS (hazards ratio: 0.87, 95% CI 0.76-1.00) in patients with MIUC compared with in the placebo/observation group. The DFS benefit was prominent in patients who underwent neoadjuvant chemotherapy (P = 0.041) and in those with bladder cancer (P = 0.013) but did not differ across programmed death-ligand 1 and lymph node status. Adjuvant ICI therapy was associated with increased risk of any (OR: 2.98, 95% CI 2.06-4.33) and severe adverse events (OR: 1.78, 95% CI 1.49-2.13). The treatment rankings revealed that pembrolizumab for DFS (84%) and nivolumab for OS (93%) had the highest likelihood of improving survival. CONCLUSIONS: Our analyses demonstrated the DFS and OS benefits of adjuvant ICIs for high-risk MIUC. Furthermore, patients with bladder cancer who underwent neoadjuvant chemotherapy appeared to be the optimal candidates for adjuvant ICIs regarding prolonged DFS. Adjuvant ICIs are the standard of care for high-risk MIUC, and differential clinical behaviors and efficacy will enrich clinical decision-making.
Keywords: inhibitory kontrolních bodů; karcinom z přechodných buněk; Urinary Bladder Neoplasms; adjuvantní chemoterapie; Carcinoma, Transitional Cell; Humans; Immune Checkpoint Inhibitors; Chemotherapy, Adjuvant; nádory močového měchýře; lidé